2013
DOI: 10.1038/nature12024
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing cocaine-induced prefrontal cortex hypoactivity prevents compulsive cocaine seeking

Abstract: Loss of control over harmful drug seeking is one of the most intractable aspects of addiction, as human substance abusers continue to pursue drugs despite incurring significant negative consequences. Human studies have suggested that deficits in prefrontal cortical function and consequential loss of inhibitory control could be crucial in promoting compulsive drug use. However, it remains unknown whether chronic drug use compromises cortical activity and, equally important, whether this deficit promotes compuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
452
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(490 citation statements)
references
References 29 publications
33
452
4
1
Order By: Relevance
“…Reduced activity in mPFC after PNE is correlated with poor impulse control and is likely to be directly related to elevated levels of drug seeking observed in ADHD and in rats that have chronically self-administered cocaine. Like prenatal nicotine, prolonged cocaine self-administration leads to mPFC hypoactivation and increased drug seeking, both of which are rescued through optogenetic stimulation of prelimbic prefrontal cortex (Chen et al, 2013). Together these results suggest that reduced firing in mPFC after exposure to prenatal nicotine might not only impair normal everyday executive control functions but increase one's predisposition to addiction (Dalley et al, 2011;Jentsch and Taylor, 1999).…”
Section: Discussionmentioning
confidence: 58%
“…Reduced activity in mPFC after PNE is correlated with poor impulse control and is likely to be directly related to elevated levels of drug seeking observed in ADHD and in rats that have chronically self-administered cocaine. Like prenatal nicotine, prolonged cocaine self-administration leads to mPFC hypoactivation and increased drug seeking, both of which are rescued through optogenetic stimulation of prelimbic prefrontal cortex (Chen et al, 2013). Together these results suggest that reduced firing in mPFC after exposure to prenatal nicotine might not only impair normal everyday executive control functions but increase one's predisposition to addiction (Dalley et al, 2011;Jentsch and Taylor, 1999).…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, context-induced reinstatement is more prominent in goal-than in sign-trackers (Saunders and Robinson, 2013). Moreover, a context paired with ethanol injections can immediately and profoundly impair the ability to exert goal-directed control (Ostlund et al, 2010), and optogenetic suppression or activation of the prelimbic cortex, which is thought to involve goaldirected computations, can abolish or re-establish sensitivity to punishments (Chen et al, 2013). There is also preliminary evidence for this in humans (Sebold et al, subm).…”
Section: Shifts Towards Model-free Learning In Addictionmentioning
confidence: 99%
“…Moreover, the effects of a dopamine D1 receptor antagonist on sign-tracking behaviour were less prominent following post-asymptotic training. However, the data on punishment sensitivity (Vanderschuren and Everitt, 2004;Deroche-Gamonet et al, 2004) and the importance of prefrontal mechanisms in the reassertion of control (Chen et al, 2013;Ostlund and Balleine, 2008;Sebold et al, subm) may also speak to the difference between habits and compulsions.…”
Section: Shifts Towards Model-free Learning In Addictionmentioning
confidence: 99%
“…Preclinical studies, eg, have demonstrated that optogenetic modulation of these mesolimbic and mesocortical circuits can modulate drug-taking behavior in a causal manner (Chen et al, 2013c;Stefanik et al, 2013). Clinical studies are now investigating repetitive TMS (rTMS) as a tool to change drug-craving and drug-taking behavior.…”
Section: Implications For Treatment Development-dorsal Medial and Latmentioning
confidence: 99%